Mediating Role of Brand Loyalty in Driving Consumer Advocacy: Evidence from the Coffee Shop Industry - Setiawan, Suryadi; Lukitaningsih, Ambar; Fadhilah, Muinah (Relevance: Journal of Management and Business, 2025)
This study examines the role of brand loyalty as a mediating variable in the relationship between brand satisfaction, brand attachment, and consumer advocacy in the modern coffee industry, using Kopi Kenangan as a case study. Empirical evidence suggests that consumer satisfaction with product and service quality does not always lead to voluntary advocacy behavior. Guided by Expectancy-Disconfirmation Theory (EDT), this study investigates how functional satisfaction and emotional attachment influence loyalty and subsequently encourage consumer advocacy. A quantitative approach was employed with purposive sampling of 150 respondents who had been active Kopi Kenangan customers for at least six months. Data were collected through an online questionnaire using a five-point Likert scale and analyzed using Structural Equation Modeling (SEM) with AMOS. The results indicate that brand satisfaction and brand attachment have a positive and significant effect on brand loyalty, while brand loyalty strongly influences consumer advocacy. Furthermore, brand loyalty mediates the relationship between brand satisfaction and brand attachment with consumer advocacy. These findings confirm that brand loyalty is shaped not only by functional satisfaction but also by a strong emotional bond between consumers and brands. This study provides practical insights for marketers to strengthen personalized brand experiences and develop emotionally driven loyalty strategies to foster sustainable consumer advocacy in the digital era.